Mechanism for creation and implementation of fractal model of human resource management: analyzing the personnel properties for demand of the organization - Kudaibergenov, Zh.; Rustamov, N.; Taizhanov, L.; Imer, S. (BUKETOV BUSINESS REVIEW, 2021)
Object: This paper considers an issue related to human resource management (HRM) in an organization from the point of view of a fractal. The paper aims is to determine the main parameters and importance of personnel management, and to create and to implement a fractal model of personnel management, which are the basis of the human resource management system in the organization. Methods: The authors used the theoretical approach from the fractal theory to determine the fractal of things, and the questionnaire method for collecting data. Obtained data was analyzed by using the formulae of fractal theory. Findings: Identifying the levels of personal properties and their manageability using the fractal HRM model is achieved in two phases. When the personnel susceptibility to control impact shows the higher meanings, it means that they are more controllable. Also, this paper determined that the control impact works if the manager uses 80 % of the force of impact. Conclusion: Using of the fractal HRM model significantly impacts on the efficiency management of the organization and identifies the real position of the personnel, that is, which one is more capable among them and how to use their abilities in favor of the organization.